RANCANG BANGUN APLIKASI KELAS EKSEKUTIF YUKNGAJI BOGOR BERBASIS WEB MENGGUNAKAN JAVASCRIPT - Raihan Hafiz Syafi; Samsuri Yahya; Suhendra Anjar Dinata (Sekolah Tinggi Ilmu Komputer El Rahma, 2025)
The utilization of information technology in da'wah activities is crucial for enhancing the effectiveness of message delivery and program management. YukNgaji Bogor, a branch of the YukNgaji da'wah community, faces challenges in managing data and monitoring the progress of Executive Class participants, which was previously done manually. This research aims to analyze the current processes, as well as design, build, and test a JavaScript-based web application using the Research and Development (R&D) method, Agile Kanban approach, Object-Oriented Programming (OOP) concepts, and Unified Modeling Language (UML). The research results in a centralized web application that facilitates participant data management and progress monitoring.